Institutional Sustainability Development of Higher Education in Indonesia - Nugraha Nugraha; Iqbal Lhutfi; Heraeni Tanuatmodjo; Fadli Agus Triansyah (Fakultas Ekonomi, Universitas Negeri Semarang, 2023)
This study examines the seven primary dimensions of higher education sustainability: Curriculum, Research and Scholarship, Operation, Faculty Staff Development and Rewards, Outreach and Service, Student Engagement, and Administration-Mission Planning. Based on Cluster 1, 2, and 3. This study looked at 146 higher education institutions (HEIs). A survey of 146 university lecturers was used to gather data and calculate the contribution of each dimension, and we used Confirmatory Factor Analysis (CFA). We discovered that HEIs' sustainability is significantly determined by faculty staff development and rewards, administration, mission, and planning. However, the Curriculum and Research Scholarship sections were the weakest. Cluster 1 HEIs had the highest rate of institutional sustainability development, followed by Cluster 2 and 3, as expected. Cluster variability and patterns are also explored to reveal differences between variables. This paper presents a study of commonalities among several sets of learning outcomes for sustainable development in higher education and examples that might help HEIs choose acceptable learning outcomes for sustainable development. This paper is intended to stimulate conversation and forward-thinking, enriching a much-needed part of sustainability education.